Analysis on agarwood vapour using headspace volatile DVB-CAR-PDMS SPME with different sampling time - Nurlaila, Ismail; Mohd Hezri, Fazalul Rahiman; Mohd Nasir, Taib; Mastura, Ibrahim; Zareen, Seema; Saiful Nizam, Tajuddin (IEEE, 2017)
Due to its popularity and high market demand, critical analysis on agarwood vapour chemical compounds may provide an alternative quality discrimination of agarwood oil. The proposed work involves the extraction of high quality agarwood using headspace volatile divinylbenzene-carboxen-polydimethysiloxane (DVB-CAR-PDMS) solid phase microextraction (SPME) with different sampling time at 15, 30 and 60 minutes. Then, Gas chromatography - Mass Spectroscopy (GC-MS) is performed to identify the chemical compounds. Generally, agarwood vapour is rich in terpene group especially monoterpene, sesquiterpene and oxygenated sesquiterpene. Analysis showed that at least 52, 50 and 54 compounds are extracted at 15, 30 and 60 minutes, respectively. Among all, duration of 60 minutes produced the highest abundance (%) for caryophellene oxide. The finding proves that caryophellene oxide as one of the important compounds in high agarwood and different sampling time plays a major role that effects the extraction. Thus, the analysis in this study is significant and brings benefit especially to the agarwood and its essential oil research area.